Physicochemical properties and in vitro starch digestibility of potato starch/protein blends. (10th December 2016) - Lu, Zhan-Hui; Donner, Elizabeth; Yada, Rickey Y.; Liu, Qiang
Highlights: Protein inhibited starch granule swelling in starch/protein blends during cooking. Short-range ordering in cooked blends increased with high blend ratio of protein. Short-range ordering in amylopectin by cooling was reversible after reheating. RS content correlated to short-range ordering in starch and blend ratio of protein. Abstract: This study aimed to investigate effects of starch-protein interactions on physicochemical properties and in vitro starch digestibility of composite potato starch/protein blends (0, 5, 10, or 15% protein) during processing (cooking, cooling and reheating). The effect on recrystallization and short-range ordering in starch was studied by light microscopy, differential scanning calorimetry and Fourier transform infrared spectroscopy. The results show that protein in the blend proportionally restricted starch granule swelling during cooking and facilitated amylopectin recrystallization during cold-storage. The facilitating effect of protein diminished with increasing blend ratio. Resistant starch content in the processed blends was positively correlated to intensity ratio of 1053/1035 cm −1 in FTIR spectra arising from slow retrogradation of amylopectin ( r 2 > 0.88, P ≤ 0.05), whose formation was favored by the presence of protein in the blends and further enhanced by cooling of cooked blends. As a conclusion, starch-protein interaction reduced starch digestibility of the processed blends.